Comparative Analysis of the Financial Performance of PT Ultrajaya Milk Industry & Trading Company Tbk and PT Diamond Food Indonesia Tbk Period 2019-2023 - Aulia, Arti Mirza; Safitri, Uhti Noer Choliza; Hidayati, Cholis (Indonesian Journal Publisher, 2025)
This study analyzes the financial performance of PT Ultrajaya Milk Industry & Trading Company Tbk (ULTJ) and PT Diamond Food Indonesia Tbk (DMND) during the 2019-2023 period. The research uses a qualitative descriptive approach with the evaluation of financial ratios, such as liquidity (current ratio and quick ratio), solvency (debt to asset ratio and times interest earned), activity (inventory turnover and receivables), and profitability (return on assets and return on equity). Data is obtained from annual financial reports published through the Indonesia Stock Exchange and the company's official website. The results of the analysis show that ULTJ excels in profitability stability with an average profit margin of 0.17 and a consistent dividend distribution policy, reflected in the Dividend Yield of 0.154 and Dividend Payout Ratio of 0.7564. On the other hand, DMND is superior in operational efficiency and asset utilization with an average total asset turnover of 1.08 and fixed asset turnover of 2.97. In addition, DMND recorded a higher Return on Equity (ROE) of 1.27, indicating a better ability to generate profit from equity. However, DMND has not distributed dividends during the analysis period, reflecting a focus on reinvestment for business development. This study concludes that ULTJ is strong in profitability and return to shareholders, while DMND excels in asset management efficiency.